Implementation of The Classical Conditioning in PAI Learning - Baharuddin Baharuddin; Suyadi Suyadi (IJECA (International Journal of Education and Curriculum Application), 2020)
SMAN 1 Teladan in the study of Islamic education uses the behavioristic theory known as classical conditioning. This research aims to determine the implementation of classical conditioning in the study of Islamic education in SMAN 1 Teladan and the factors that influence it. The study used qualitative research with a case study approach. Data collection is conducted using observation methods and interviews. The results showed that the application of classical conditioning in PAI learning was done through several stages, namely (1) making the classroom atmosphere comfortable. The stage is to give students the freedom to express their opinions during the discussion, slip intermezo in the material explanation, sometimes using English in material explanations, and the use of LCD in the Learning. (2) assigning continuous tasks. Assignments are given in the form of group discussions and Kultum. Students perform the Kultum when the teacher prepares the teaching materials. In addition, the stimulus makes students active in learning. The factors that influence it are factors of the teacher, teachers have the ability to understand the psychology of students so that he understands the theory or the right method to use. Student factors, students have a sense of responsibility for a given assignment, and complementary attitudes in a cult assignment. Institutional factors, institutions or schools that support in terms of vision and mission and school policies.